ASSISTANCE IN DEVELOPING E-COMMERCE AND SIMPLE FINANCIAL RECORDING FOR SMES IN ACEH UTARA - Raudhatinur; Venna Maulida Mustika; Yusnidar (RADJA PUBLIKA, 2025)
This community service program aims to enhance the capacity of Micro, Small, and Medium Enterprises (SMEs) in Keude Geudong, North Aceh, through training and mentoring in e-commerce development and simple financial recording. The background of this program is based on the low level of digital adoption and limited financial management practices among SMEs, which hinder their business growth and sustainability. The method used in this program consists of training and continuous mentoring. The training phase focuses on introducing e-commerce platforms, digital marketing strategies, and the importance of simple bookkeeping. Meanwhile, the mentoring phase is conducted to assist participants in the practical implementation of e-commerce and financial recording in their daily business activities. The results of this program show a significant improvement in participants’ knowledge and skills. SMEs are able to create and manage online stores, expand their market reach through digital platforms, and apply simple financial recording practices, including documenting income and expenses. In addition, participants demonstrate increased awareness of the importance of separating personal and business finances. In conclusion, the integration of training and mentoring is effective in improving digital capabilities and financial management of SMEs. This program contributes to strengthening business performance and supports the sustainability of SMEs in the digital era.